Capital flight from Africa : causes, effects, and policy issues - Ajayi, Simeon Ibidayo; Ndikumana, Léonce (Oxford 6 Oxford University Press, 2015)
This edited collection provides the most comprehensive thematic analysis of capital flight from Africa, covering economic and institutional aspects, as well as domestic and global dimensions. It is organized in three parts. The first part discusses the importance of capital flight in the context of the development policy discourse at national and international level. This part takes stock of the existing evidence on the nature, causes, and consequences of capital flight. It provides the most recent data on the magnitude of capital flight from 39 African countries, and a detailed analysis of the impact of capital flight on economic development in general and on poverty reduction in particular. The second part examines economic factors and impacts of capital flight. It presents analysis of capital flight in a flow of funds context, the impact of capital flight on macroeconomic outcomes with a focus on growth, and the linkages between capital flight and monetary policy, financial liberalization, and the global financial system. The third part explores the domestic and international institutional environment and its relevance for capital flight and stolen asset recovery. It discusses the role of governance, tax evasion, and secrecy jurisdictions in driving capital flight. The last part of the book offers suggestions for strategies to address the problem of capital flight from African countries.
Includes bibliographical references and index.
aia 24/10/17
Loans
Keywords: Capital movements; Africa